ROLE OF DIVIDEND POLICY IN CAPITAL MARKET - Sherkuzieva Nasiba Abrorovna (American Journals, 2025)
This article studies role of dividend policy in capital market. Moreover, effects of dividend policy in capital market, dividend payout statistics for companies listed on the New York Stock Exchange (NYSE) are analyzed in detail. Scientific conclusions and recommendations are presented on the basis of analyses.
Keywords: Dividend, dividend payout, dividend policy, stock, capital, capital market, securities.